Decent Work and Work Engagement: A Profile Study with Academic Personnel - Graça, Marta (2020)
This study analyses the relationship between Decent Work and Work Engagement in Portuguese and Brazilian higher education teachers/researchers, and aims to identify distinct emergent profiles resulting from the relationship between these variables. The sample is composed of 749 participants and data was collected online, in both Portugal and Brazil, using the Decent Work Questionnaire (DWQ) and the Utrecht Work Engagement Scale (UWES). Results of multiple linear regressions showed that Decent Work dimensions positively predict Work Engagement in all its three dimensions (Vigor, Dedication, and Absorption). Profiles of workers regarding Decent Work dimensions were created using cluster analysis. Differences regarding Work Engagement and its respective dimensions were analyzed through a MANOVA. The results help organizations to apply new strategies and policies to promote higher levels of decent work, especially the Opportunities dimension to make their workers feel more engaged with their work. Limitations and directions for future research are considered.